Makespan of routing and security in Cross Centric Intrusion Detection System (CCIDS) over black hole attacks and rushing attacks in MANET. Issue 4 (14th October 2019) - N., Rajendran; P.K., Jawahar; R., Priyadarshini
Abstract : Purpose: The purpose of this paper is to apply security policies over the mobile ad hoc networks. A mobile ad hoc network refers to infrastructure-less, persistently self-designing systems; likewise, there is a noteworthy innovation that supplies virtual equipment and programming assets according to the requirement of mobile ad hoc network. Design/methodology/approach: It faces different execution and effectiveness-based difficulties. The major challenge is the compromise of performance because of unavailable resources with respect to the MANET. In order to increase the MANET environment's performance, various techniques are employed for routing and security purpose. An efficient security module requires a quality-of-service (QoS)-based security policy. It performs the task of routing and of the mobile nodes, and it also reduces the routing cost by finding the most trusted node. Findings: The experimental results specify that QoS-based security policy effectively minimizes the cost, response time as well as the mobile makespan (routing cost and response time) of an application with respect to other existing approaches. Research limitations/implications: In this paper, the authors proposed an enhancement of Cross Centric Intrusion Detection System named as PIHNSPRA Routing Algorithm (PIHNSPRA). Practical implications: It maps the security with the secure IDS communication and distributes the packets among different destinations, based on priority. This calculation is proposed for the purpose of routing and security by considering greatest throughput with least routing cost and reaction time. Social implications: When the concept is applied to practical applications. Quality of Service introduced in the proposed research reduces the cost of routing and improves the throughput. Originality/value: The proposed calculation is tested by NS2 simulator and the outcomes showed that the execution of the calculation is superior to other conventional algorithms.